2012
DOI: 10.1007/s10695-012-9753-7
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolism in European sea bass (Dicentrarchus labrax): effects of n-6 PUFA and MUFA in fish oil replaced diets

Abstract: Monounsaturated fatty acids (MUFA)-rich and n-6 polyunsaturated fatty acid (n-6 PUFA)-rich vegetable oils are increasingly used as fish oil replacers for aquafeed formulation. The present study investigated the fatty acid metabolism in juvenile European sea bass (Dicentrarchus labrax, 38.4 g) fed diets containing fish oil (FO, as the control treatment) or two different vegetable oils (the MUFA-rich canola/rapeseed oil, CO; and the n-6 PUFA-rich cottonseed oil, CSO) tested individually or as a 50/50 blend (CO/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 46 publications
9
32
2
1
Order By: Relevance
“…In a similar study on sea bass, Izquierdo et al (2003) reported that the replacement of 60% of fish oil with linseed oil (n-3 PUFA-rich), soybean oil (n-6 PUFA-rich), rapeseed oil (MUFA-rich) and a mixed-blend did not negatively impact on fish performance, when high lipid content (25%) diets were evaluated. As in many instances, this result is similar to a number of the other earlier studies with European sea bass and salmonids where the complete replacement of dietary fish oil with alternative vegetable oils has resulted in no affect on fish growth performance (Guillou et al, 1995;Tocher et al, 2000;Torstensen et al, 2000;Bell et al, 2001, Mourente et al, 2005bTurchini et al, 2011b;Eroldoğan et al, 2012;Eroldoğan et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In a similar study on sea bass, Izquierdo et al (2003) reported that the replacement of 60% of fish oil with linseed oil (n-3 PUFA-rich), soybean oil (n-6 PUFA-rich), rapeseed oil (MUFA-rich) and a mixed-blend did not negatively impact on fish performance, when high lipid content (25%) diets were evaluated. As in many instances, this result is similar to a number of the other earlier studies with European sea bass and salmonids where the complete replacement of dietary fish oil with alternative vegetable oils has resulted in no affect on fish growth performance (Guillou et al, 1995;Tocher et al, 2000;Torstensen et al, 2000;Bell et al, 2001, Mourente et al, 2005bTurchini et al, 2011b;Eroldoğan et al, 2012;Eroldoğan et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…However, in marine fish feeds the use of vegetable oils as the sole lipid source is limited by the low ability of these species to convert α-linoleic (LA,) and linolenic (LNA,, abundant in many plant oils, into arachidonic (ARA, 20:4n-6), eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA,. Thus, the partial replacement of fish oil by vegetable oils would be only possible when these fatty acids are present in the diets in sufficient levels to meet essential fatty acid requirements, which can generally be achieved when fishmeal is included in the diet in the range of 30 -50% Benedito-Palos et al, 2008;Ng and Gibon 2010;Eroldoğan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations